PENGEMBANGAN DESA WISATA KENDERAN BERBASIS KEARIFAN LOKAL TRI HITA KARANA: PENGEMBANGAN DESA WISATA KENDERAN BERBASIS KEARIFAN LOKAL TRI HITA KARANA - Januarta, I Dewa Gede Ari; Lilasari, Luh Nyoman Tri (Journal of Applied Science in Tourism Destination, 2025)
Kenderan Tourism Village, which emphasizes local wisdom based on Tri Hita Karana, has the potential to be an important sector in the development of village tourism, with this study aiming to explore the development of tourism destinations based on such local wisdom using qualitative descriptive methods through observation, literature study, and interviews, as well as SWOT and IFAS EFAS analysis; The results showed that development strategies include creating tour packages with collaboration and technology for promotion (SO), training and cooperation with youth to protect the environment and improve facilities (WO), creating regulations for land use change and tourism supervision (ST), and improving human resources and quality of facilities (WT), with an IFAS score of 3.01 (good/strength) and EFAS of 3.10 (good/opportunity), indicating that aggressive strategies, especially the short-term strategy S-O, are the most supportive of Kenderan Village's growth.